Information And Communication Technology- Based Learning Models In Islamic Religious Education - Liana Nurhaeti (DIROSAT: Journal of Education, Social Sciences & Humanities, 2023)
Learning media is a very important factor in the teaching and learning process. Education emphasizes very systematic and strict control over the learning process, by giving educators the flexibility to develop strategies, methods and learning media. In fact, learning media can make it easier for educators to deliver subject matter and make it easier for students to understand the subject matter. Based on the reality above, researchers are trying to explore Information and Communication Technology -based learning media models in Islamic religious education. This research was made to find out ICT-based learning media in Islamic religious education according to husniyatus salamah zainiyati and to find out ICT-based learning models in Islamic religious education in today's digital era. The type of this research is library research, which is conducting a thorough study of the literature related to the subject matter, which in this case is information and communicatin technology -based learning media . In this research the data obtained will be analyzed using descriptive analysis method. The data collected and compiled is then analyzed. This analysis is useful for the writer as a further exploration of the problem of ICT-based learning media models in Islamic Religious Education. The conclusion of this study is that information and communication technology -based learning models for Islamic religious education according to Husniyatus Salamah Zainiyati are computer-based learning, internet-based learning, and multimedia-based learning which are widely used as learning models in the current modern era, namely the era of covid-19 . The Covid-19 pandemic has forced educators to use internet-based learning or what we know as E-learning which has various variations of the online learning system.